ASMAUL HUSNA DALAM KRIYA UKIR KAYU - Alfata Zaqqi; Syafei Syafei (Universitas Negeri Padang, 2019)
The purpose of the creation of the final work is to visualize Asmaul Husna's calligraphy in carving with wood carving techniques. The methods used are: preparation, elaboration, synthesis, concept realization, and finally completion. At the end of this final work, an exhibition was held. the media used in making this final work is wood. The seven works that were made include: Ar-Rahman, Ar-Raheem, As-Salam, Al-Ghaffar, Ar-Razzaq, Al-Wahhab, Al-Adl, is a theme that was raised from the Compassion of Allah. if you understand and practice Asmaul Husna, you will feel calm in everyone.Keywords: Asmaul Husna, carving, wood carving techniques.